(untitled) - Gregory J. E Rawlins (New York, 1991)
The book covers a segment of the classical material on data structures and algorithms. It covers all the essentials of algorithms analyisis in an innovative problem-oriented style; focuses on the basic programming problem and works through a variety of options for its solution rather than simply stating a correct answer
Keywords: computer algorithms